(untitled) (Journal of Academic Research, 2022)
Bacterial urinary tract infections (UTI) are among the most common infections in worldwide. among different patients, women infection is the higher. This study aimed to determine the bacterial agents of women with urinary tract infection from al khums city in Libya, and testing the susceptibility of bacterial strains isolated from patients visited the Soug Alkamees Central Hospital Methods: During February 2021 to April 2021 and using standard microbiological techniques, we examined 120 urine specimens collected from women with UTI and 30 specimens from women without UTI as control. The BD Phoenix Automated Microbiology System were used to identify and determine the susceptibility of bacterial isolates against antimicrobial agents. Our results were collected and analyzed using SPSS version 20 software. P- value ≤ 0.05 was considered statically significant. Results: We detected a causative agent in 53/120 patients (44.2%).The most frequently isolated uropathogenic bacteria from women with urinary tract infection were Escherichia coli 19/53 (35.8%), klebsiella pneumonia 14/53 (26.4%) and Enterococcus faecalis 9/53 (17 %). Bacterial isolates showed very high resistant rates (100%) to different antibiotics. On the other hand, all strains were susceptible to another antibiotics.